NOMADIC ENVIRONMENT: ISSUES AND SECURITY THREATS - Chirag Jain, Neha singh, Rajiv Chechi (International Journal of Advanced Science and Technology, 2020)
This paper is basically a study of issues raised during connection of global internet environment or specified fixed stored resource while moving around from one place to another i.e. nomadic environment. Here we have discussed various issues/ security threats and some protection mechanism to make nomadic computing more secure.